Valuation of Investment Companies in Chile - Maquieira V., Carlos; Zurita L., Salvador; García O., Valeria; Velasco D., María Luisa (Estudios de Administración, 2003)
Though no clear definition of investment companies exists in Chile, it has been generally understood to refer to companies that have investments in other companies (with or without corporate control) but that do not own productive assets. A question that naturally arises is whether the market value of investment companies is equal to the economic value of the assets in which they invest, and if not, what factors account for the difference. International evidence indicates that for conglomerates a discount on market value would exist and also the situation would be similar (although not identical) to closed-end funds. In this paper we study the existence and explanation of a discount to Chilean investment companies. We find an average discount of 28% in a sample of 22 investment companies studied in the period December 1993 -- December 1999; and the structure of premiums and discounts is explained in an 83% by four variables. The results reported in this study are consistent with the following hypotheses: The discount of the investment companies is positively related to the percentage of insider ownership (insiders can maximise its wealth to the detriment of outsiders). On the other hand, it is negatively related to: the investment in filiated and related companies, the amount invested in investment companies maintained in the portfolio (probably due to an agency problem among shareholders), and the Depurate Book Value of Assets (a regulatory accounting restriction that affects Chilean pension fund investments).